Hazel Motes, war veteran: “Wise blood” and the early theorization of shell-shock - Kuhn, Joseph (Litteraria Copernicana, 2025)
The article claims that Hazel Motes in Flannery O’Connor’s novel Wise Blood is a veteran of the Second World War. He fought in the desert war in North Africa in 1943. The desert war was notable for its large number of cases of mental breakdown amongst American troops and the unusual psychology of Hazel might reflect post-traumatic stress disorder. The article argues that Motes’s participation in the war forms an essential foundation for O’Connor’s drama of salvation in the novel. O’Connor follows one of her favourite theologians, Karl Barth, in showing how the sudden, violent bestowal of God’s grace on Motes is like a military assault and produces in him theological shock. Streszczenie W artykule zawarto tezę, że Hazel Motes w powieści Flannery O’Connor „Mądrość krwi” jest weteranem II wojny światowej. Brał udział w wojnie pustynnej w Afryce Północnej w 1943 roku. Wojna pustynna charakteryzowała się dużą liczbą przypadków załamania psychicznego wśród żołnierzy amerykańskich, aliencja Hazel mogła odzwierciedlać zespół stresu pourazowego. W artykule wykazano, że udział Motesa w wojnie stanowi istotny fundament powieściowego dramatu zbawienia u Flannery O’Connor. O’Connor podąża za jednym ze swoich ulubionych teologów, Karlem Barthem, pokazując, jak gwałtowne obdarzenie Motesa łaską Bożą przypomina atak militarny i wywołuje u niego nagłe teologiczne objawienie.